Surgical Management of the Metastatic Spine Disease: A Review of the Literature and Proposed Algorithm. Issue 2 (March 2023) - Al Farii, Humaid; Aoude, Ahmed; Al Shammasi, Ahmed; Reynolds, Jeremy; Weber, Michael
Study Design: Narrative Review. The spine remains the most common site for bony metastasis. It is estimated that up to 70% of cancer patients harbor secondary spinal disease. And up to 10% will develop a clinically significant lesion. The last two decades have seen a substantial leap forward in the advancements of the management of spinal metastases. What once was a death sentence is now a manageable, even potentially treatable condition. With marked advancements in the surgical treatment and post-operative radiotherapy, a standardized approach to stratify and manage these patients is both prudent and now feasible. Objectives: This article looks to examine the best available evidence in the stratification and surgical management of patients with spinal metastases. So the aim of this review is to offer a standardized approach for surgical management and surgical planning of patients with spinal metastases.